Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1042/bst0340696
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms controlling the expression of the components of the exocytotic apparatus under physiological and pathological conditions

Abstract: The last decade has witnessed spectacular progress in the identification of the protein apparatus required for exocytosis of neurotransmitters, peptide hormones and other bioactive products. In striking contrast, our knowledge of the mechanisms determining the expression of the components of the secretory machinery has remained rudimentary. Since modifications in secretory functions are associated with several physiological processes and contribute to the development of human pathologies, a better knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
(48 reference statements)
0
20
0
Order By: Relevance
“…Mir-124a affects the expression of a number of other exocytosis related proteins in MIN6 B1 cells including SNAP25, Rab3A, synapsin-1A, Rab27A and Noc2; although only Rab27A is a direct target of mir-124a [4]. These exocytosisrelated proteins also have predicted binding sites for regulation by other miRNAs, but these still remain to be experimentally validated [22].…”
Section: Introductionmentioning
confidence: 99%
“…Mir-124a affects the expression of a number of other exocytosis related proteins in MIN6 B1 cells including SNAP25, Rab3A, synapsin-1A, Rab27A and Noc2; although only Rab27A is a direct target of mir-124a [4]. These exocytosisrelated proteins also have predicted binding sites for regulation by other miRNAs, but these still remain to be experimentally validated [22].…”
Section: Introductionmentioning
confidence: 99%
“…The same element is also repressed by high concentrations of palmitate, in vitro and in vivo (4). The effects of both glucose and palmitate are mediated by the cAMP-dependent overexpression of the inducible cAMP early repressor repressor ICER-1, which adversely affects ␤-cell function and proliferation (1,4,6,232,233). If the same effect was to occur in human ␤-cells exposed to long-term hyperglycemia, a logical therapeutic measure would be to restore normal levels of Cx36.…”
Section: F Cx36 and Diabetesmentioning
confidence: 99%
“…Myotrophin is evidently the target of miR-375, and this miRNA:target interaction regulates the secretion of insulin. The regulation of exocytosis machinery is probably a widespread phenomenon because many miRNAs are predicted to target exocytosis-related proteins [41]. Plaisance et al [54] showed that miR-9 causes a reduction in exocytosis in pancreas (insulinsecreting beta cells) that is elicited by stimuli including glutamate.…”
Section: Regulation Of Metabolic Biochemistry In Mammalsmentioning
confidence: 99%
“…Accordingly, miRNAs participate in metabolism--making energy available to an organism. Thus far research in this field is in its infancy, and much remains to be learned (for excellent prior reviews, see [41][42][43][44]). Some research findings will be summarized below with an emphasis on the metabolism of lipids.…”
Section: Research On the Role Of Mirnas In Metabolismmentioning
confidence: 99%